Acoustic emission-based transition monitoring of mechanical mechanism for bolted shear connection in GFRP–UHPC hybrid beams. (July 2022) - Li, Sheng-Li; Kang, Zhuang-Zhuang; Wu, Guang-Ming; Guo, Pan; Gu, Sheng
Highlights: AE could monitor the transition of mechanical mechanism of GFRP–UHPC hybrid beams. AE signals with high peak frequencies could reflect the plastic deformation of HSBs. The intensive degrees of b-value points in distinct loading stages are different. AE intensity analysis could quantitatively assess the damage degree of the specimen. Abstract: The failure of glass fiber reinforced polymers (GFRP)–ultra-high performance concrete (UHPC) hybrid beams originate from its mechanical mechanism transition, which is reflected in the plastic deformation of its components. The plastic deformation could be sensitively detected using acoustic emission (AE) technique. In this study, AE technique was utilized to monitor the mechanical mechanism transition of the GFRP–UHPC hybrid beam through the push-out test of a bolted shear connection specimen. Results showed that AE parameters could reflect the damage transition of the push-out specimen from qualitative and quantitative perspectives. First, the variation characteristics of AE hits, energy, and ringing counts were remarkably discernible in the three loading stages of the specimen. And the plastic deformation of high-strength bolts could be identified by the increase in AE signals with high peak frequencies. Besides, the mechanical mechanism transition of the specimen could be distinguished by the intensive degrees transition of b-value points in the different loading stages. Finally, the boundary values of the historic index [ H ( t ) ] and severity ( S r ) were proposed to quantitatively evaluate the damage degree of the specimen. AE technique provides a possibility of safety warning for the GFRP–UHPC hybrid beams because of its ability to effectively identify the mechanical mechanism transition.